Mapping causal knowledge: How managers consider their environment during meetings. (24th June 2009) - Shaw, Duncan; Eden, Colin; Ackermann, Fran
Causal mapping can help managers to think through the causal influence between issues, enabling them to base a decision on a more structured consideration. Even in regular meetings, learning and the integration of knowledge from diverse stakeholders can benefit from causal mapping. Four causal mapping meetings with management teams are analysed to assess how managers thought causally about their environment when strategy-making. We found that although managers can use other views to expand their environmental knowledge, some prefer to use familiar information rather than less familiar information. Despite this preference, many managers thought systemically about a raft of related issues. We discuss our findings in the context of regular meetings and offer improvements to the facilitation of group causal mapping.